Genital Tract Infections, Bacterial Vaginosis, HIV, and Reproductive Health Issues among Lima-Based Clandestine Female Sex Workers - M. E. Perla; Annette E. Ghee; Sixto Sánchez; R. Scott McClelland; Annette L. Fitzpatrick; Luis Suárez-Ognio; Javier R. Lama; Jorge Sánchez (Hindawi Limited, 2012)
Sociodemographic and behavioral characteristics of 212 Peruvian female sex workers (FSWs) were analyzed. The association between genital tract infections (GTIs) and risk factors by multivariate analysis was evaluated. Eighty-eight percent of FSWs were diagnosed with at least one GTI (HSV-2 80.1%, BV 44.8%, candidiasis 9.9%, syphilis seropositivity 9.4%, Trichomonas vaginalis 2.4%, HIV seropositivity 2.4%). Reported condom use with clients was nearly universal (98.3%), but infrequent with husband/regular partners (7.3%). In multivariate analysis BV was negatively associated with more consistent condom use (PRR=0.63, 95% CI, 0.42-0.96). Many had not visited a Sexually Transmitted Infection (STI) clinic or been tested for HIV in the past year (40.6%, 47.1%, resp.). Nonclient contraceptive use was low (57%) and induced abortion was common (68%). High GTI burden and abortions suggest that a services-access gap persists among marginalized FSWs. Continued health outreach programs and integrating family planning and reproductive health services into existing STI clinic services are recommended.